ISTORIA GÂNDIRII PEDAGOGICE JEAN-JACQUES ROUSSEAU (1712-1778) - USM ADMIN (Moldova State University, 2008)
Historical analysis of a negative pedagogy promoted by J. Jaques Rousseau in his educational treatise "Emile" (1762) marks out the author's capacity of psycho-centrist paradigm anticipation which was developed between XIX and XX century boundary by the current New education. Education centered on concrete capture of child presumes his intern recourses capitalization and extern social influences avoidance considered harmful for the formative background.